Evaluation of Bread Wheat Genotypes Using Various Stress Indices for Heat Resilience - Beniwal, Jogender; Kumar, Krishan; Arya, Rajesh Kumar; Lakra, Nita; Kumari, Anita; Kathwal, Rajesh (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during rabi seasons (November to April of 2022–2023 and 2023–2024) at Research Area of the Department of Genetics and Plant Breeding, CCS Haryana Agricultural University, Hisar, Haryana, India to evaluate 205 wheat genotypes, including five checks in augmented design under normal (timely sown) and heat stress (late sown) conditions for heat resilience using six stress indices. Results revealed a significant reduction in grain yield under heat stress conditions. Six stress indices viz. heat susceptibility index, mean productivity, tolerance, stress tolerance index, yield stability index and yield index were calculated based on grain yield under timely and late sown conditions to classify genotypes into tolerant and susceptible categories. Correlation analysis indicated a positive and highly significant association between grain yield under timely sown conditions and heat susceptibility index, mean productivity, tolerance, stress tolerance index and yield index whereas a negative and highly significant association was observed with yield stability index. Conversely, grain yield under heat stress conditions was positively and significantly correlated with yield stability index, mean productivity, tolerance, stress tolerance index and yield index but negatively and significantly associated with heat susceptibility index. Based on heat susceptibility index, 119 genotypes were classified as heat-tolerant and 86 as heat-susceptible ones. Among the tested genotypes, Raj 2184 exhibited the highest heat tolerance whereas HUW 12 was the most heat-sensitive. Therefore, genotype Raj 2184 could be effectively utilized in breeding programs for developing heat-tolerant wheat varieties, cultivation under high-temperature conditions and as a genetic resource for enhancing stress tolerance in wheat.